Dual-functionality of Thauera sp. JM12B12: aerobic denitrification and bioflocculation for nitrogen and suspended particles removal at low carbon-to-nitrogen ratios - Zhang, Mingxia; Zhang, Yulian; Yao, Qing; Hu, Yanna; Zhu, Honghui (Frontiers in Microbiology, 2025)
Denitrifying bacteria with flocculation capacity were dual-function microorganisms that can simultaneously remove nitrogen (N) and reduce suspended particles in wastewater, providing a sustainable bioremediation strategy. In this study, a novel denitrifying bacterium capable of producing bioflocculants, Thauera sp. JM12B12, was isolated and investigated. The results confirmed that this strain could completely remove NO3−-N and NO2−-N under microaerobic conditions with a low C/N ratio of 5, using lactate as the optimal carbon source. Notably, no other harmful inorganic N species were produced during denitrification, and total N removal efficiency consistently exceeded 93.0%. Optimal denitrification conditions include a pH range of 7–9, salinity of 0–1.5%, temperature of 25–40 °C, and static incubation. Remarkably, this strain synthesized extracellular bioflocculants during NO3−-N removal, achieving 91.4% flocculation efficiency with cell-free supernatant. Genome analyses revealed a complete denitrification pathway (possessing napA, two nirS, norB, nosZ) and 80 bioflocculant-related genes (polysaccharide production and protein secretion), highlighting its dual capacity for N and suspended particle removal. PCR also confirmed key denitrification genes. Therefore, JM12B12 could be a multifunctional microbial agent for N removal and flocculation, offering a sustainable solution for low C/N wastewater treatment, particularly valuable in recirculating aquaculture systems.